Human Resource Development: Quality Of Educators And Teacher Meetings Subjects In Madrasa - Mardiyah, Siti; Subandi, Subandi; Hadiati, Eti (Journal of Advanced Islamic Educational Management, 2023)
There are fundamental problems in the world of education regarding human resources that have not fully developed the potential stored in each educator. Research on human resource management with its operational functions emerged as a strategy to manage human resources to have optimal competence and performance in achieving common goals. this study aims to obtain an overview of Human Resource Development in Improving the Quality of Educators through Subject Teacher Deliberations at Madrasa Aliyah Negeri Lampung Utara, Indonesia. Research data were obtained through the process of interviews, observation, and documentation. Data analysis was carried out using qualitative analysis stages, namely: data reduction, data presentation, conclusions, and data verification. the results showed that the development of human resources through the Subject Teacher Conference (MGMP) of Madrasa Aliyah Negeri (MAN) Lampung Utara was as follows: 1) Planning starts from the work program meeting stage, then making a work program. 2) Implementation of MGMP activities which include the preparation of learning tools, development of media and learning resources, development of strategies and media and learning resources, development of strategies and methods of learning strategies and methods, and preparation and development of evaluations. 3) Evaluation of the results of HR development policies through subject-teacher meetings (MGMP).